Prevalence of SHANK3 variants in patients with different subtypes of autism spectrum disorders - Boccuto, Luigi (Nature Publishing Group, 2013)
Autism spectrum disorders (ASDs) include three main conditions: autistic disorder (AD), pervasive developmental disorder, not otherwise specified (PDD-NOS), and Asperger syndrome. It has been shown that many genes associated with ASDs are involved in the neuroligin–neurexin interaction at the glutamate synapse: NLGN3, NLGN4, NRXN1, CNTNAP2, and SHANK3. We screened this last gene in two cohorts of ASD patients (133 patients from US and 88 from Italy). We found 5/221 (2.3%) cases with pathogenic alterations: a 106 kb deletion encompassing the SHANK3 gene, two frameshift mutations leading to premature stop codons, a missense mutation (p.Pro141Ala), and a splicing mutation (c.1820-4 G>A). Additionally, in 17 patients (7.7%) we detected a c.1304+48C>T transition affecting a methylated cytosine in a CpG island. This variant is reported as SNP rs76224556 and was found in both US and Italian controls, but it results significantly more frequent in our cases than in the control cohorts. The variant is also significantly more common among PDD-NOS cases than in AD cases. We also screened this gene in an independent replication cohort of 104 US patients with ASDs, in which we found a missense mutation (p.Ala1468Ser) in 1 patient (0.9%), and in 8 patients (7.7%) we detected the c.1304+48C>T transition. While SHANK3 variants are present in any ASD subtype, the SNP rs76224556 appears to be significantly associated with PDD-NOS cases. This represents the first evidence of a genotype–phenotype correlation in ASDs and highlights the importance of a detailed clinical-neuropsychiatric evaluation for the effective genetic screening of ASD patients.